Electronically tuned defective Prussian-blue on graphene for electrochemical water splitting. (5th August 2022) - Begum, Halima; Jung, Seunghun
Abstract: Exploiting high-performance and stable bifunctional electrocatalysts is highly desirable for water splitting applications to obtain large-scale renewable and clean fuels. Herein, a defective Prussian-blue (δ-PB or Fe III 1.23 [Fe II 1.12 (CN)6 ]0.87 ·δ0.13 ) on graphene composite electrocatalyst was fabricated through a facile hydrolytic precipitation process, followed by a single-step carbonization treatment at 600 °C (denoted as δ-PB/G-600). The resultant optimized δ-PB/G-600 exhibits remarkable electrocatalytic water splitting in alkaline media, producing lower overpotentials of 189 and 105 mV at a current density of 10 mA cm −2 for the oxygen evolution reaction and hydrogen evolution reaction, respectively. Most importantly, the δ-PB/G-600 shows remarkable durability for both reactions. The remarkable electrocatalysis was attributed to the abundant active sites and high electrical conductivity with a defective nature, which not only facilitate the electrolyte flux but also maintain the structural stability of δ-PB/G-600. Additionally, the high surface area confirms the facile mass transport and prompts the gaseous release of the composite. Highlights: Defective Fe III 1.23 [Fe II 1.12 (CN)6 ]0.87 ·δ0.13 δ-PB/G bifunctional catalyst for OER and HER. A small overpotentials of 189 and 105 mV at j 10 for the OER and HER. δ-PB/G own abundant active sites, high electrical conductivity with defects.